Gait characteristics and factors associated with fall risk in patients with dementia with Lewy bodies - Su, Zhou; Liu, Mengran; Kuai, Jun; Yi, Tingting; Zheng, Yuechang; Wang, Congcong; Peng, Junyu; Tian, Xiaojun (Frontiers in Neurology, 2025)
ObjectiveTo investigate the association between gait parameters and cognitive decline in patients with dementia with Lewy bodies (DLB) and evaluate the impact of gait abnormalities on fall risk.MethodsThis cross-sectional study enrolled 63 DLB patients. Gait analysis, including gait speed, stride length, gait symmetry, and swing time, was performed using a pressure-sensing walkway. Cognitive function was assessed using the MoCA and MMSE. Spearman correlation analysis and multiple linear regression models were used to examine the relationship between gait parameters and cognitive function. Logistic regression models, adjusted for potential confounders, were employed to analyze the effect of gait abnormalities on fall risk.ResultsGait speed showed significant positive correlations with MoCA score (p = 0.001) and stride length (p = 0.003), and a positive correlation with MMSE score (p = 0.005). Gait symmetry was weakly positively correlated with MMSE score (p = 0.027). Patients with MoCA scores below 20 exhibited a 22% reduction in gait speed (p = 0.002), shortened stride length (p = 0.001), decreased gait symmetry (p = 0.034), and prolonged swing time (p = 0.021) compared to those with higher scores. Logistic regression analysis revealed that for each 1 standard deviation decrease in gait speed, fall risk increased by 33% (p = 0.001). For each 1-cm decrease in stride length, fall risk increased by 21% (p = 0.025). For each 1-unit decrease in gait symmetry, fall risk increased by 28% (p = 0.007). Patients with a history of falls demonstrated more pronounced gait deterioration. Specifically, patients with more than 2 falls exhibited a 13% reduction in stride length (p = 0.011) and a 12% prolongation in swing time (p = 0.022).ConclusionGait abnormalities are associated with cognitive decline, and reduced gait speed and gait asymmetry are markers of cognitive decline and increased fall risk in patients with established DLB.